2021
DOI: 10.18291/njwls.127867
|View full text |Cite
|
Sign up to set email alerts
|

Young Workers on Digital Labor Platforms: Uncovering the Double Autonomy Paradox

Abstract: Drawing on interviews with 12 young adults in the Danish digital labor market, this article investigates how young workers on digital labor platforms experience the tension between ‘algorithmic management’ and autonomy. Digital labor platforms promise autonomy to workers, but the study shows that the platforms in varying degrees exert control over the labor process in different stages of the work. The inherent non-transparency of the algorithmic management systems makes it difficult for the young workers to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
1
13
0
3
Order By: Relevance
“…We have chosen to label this group as new labor market entrants primarily due to their age and employment status. These variables indicate that this group are in a phase of their life cycle, where they have just entered the labor market and they will most likely shift labor market position later in their career, as we know that young people tend to be highly mobile (Sloth Laursen et al 2021). These findings are, however, not surprising, as young people with limited career trajectories tend to be overrepresented among other groups of non-standard workers and thus the so-called periphery segment on the labor market according to much segmentation and platform studies, as well as in line with our expectations (Berg 2016;Healy et al 2017;Pesole et al 2018).…”
Section: Results: Patterns Of Hybridity Among Three Classes Of Platfo...mentioning
confidence: 99%
See 1 more Smart Citation
“…We have chosen to label this group as new labor market entrants primarily due to their age and employment status. These variables indicate that this group are in a phase of their life cycle, where they have just entered the labor market and they will most likely shift labor market position later in their career, as we know that young people tend to be highly mobile (Sloth Laursen et al 2021). These findings are, however, not surprising, as young people with limited career trajectories tend to be overrepresented among other groups of non-standard workers and thus the so-called periphery segment on the labor market according to much segmentation and platform studies, as well as in line with our expectations (Berg 2016;Healy et al 2017;Pesole et al 2018).…”
Section: Results: Patterns Of Hybridity Among Three Classes Of Platfo...mentioning
confidence: 99%
“…Some have even argued that digital platforms can have disruptive effects on the labor market due to these changes (Danish Disruption Council 2019;Hauben et al 2020;Urzi Brancati et al 2019). This is also the case in the Nordic countries, where the first empirical studies of platform work highlight work practices characterized by new forms of flexibility with associated social risks (Jesnes 2019;Oppegaard 2020;Sloth Laursen et al 2021).…”
mentioning
confidence: 90%
“…The first is that it is currently expanding globally, particularly in countries such as Spain (an estimated 18% are platform workers) or the UK [ 28 ]. Secondly, it is a form of work that is often considered to be the “future of work” [ 29 ]. The conditions of the COVID-19 pandemic have led to an expansion of these work models, which indicates that this is a perspective that is becoming established, thus the importance of legislating and analysing it in depth.…”
Section: Towards a Characterisation Of Platform Workmentioning
confidence: 99%
“…Although the scientific literature needs to explore these economic models in more depth, it has already been found that their associated occupational risks include a loss of job control and low autonomy [ 29 ], an increase in job insecurity [ 16 ] and a decline in employment-derived income [ 29 ]. This is related to the phenomenon of in-work poverty, defined as those people who are employed but do not earn above the poverty line.…”
Section: Psychosocial Risksmentioning
confidence: 99%
See 1 more Smart Citation